Nucleotide transmitters ATP and ADP mediate intercellular calcium wave communication via P2Y(12/13) receptors among BV-2 microglia - Jiang, Pengchong (PLoS One, 2017)
Nerve injury is accompanied by a liberation of diverse nucleotides, some of which act as ‘find/eat-me’ signals in mediating neuron-glial interplay. Intercellular Ca(2+) wave (ICW) communication is the main approach by which glial cells interact and coordinate with each other to execute immune defense. However, the detailed mechanisms on how these nucleotides participate in ICW communication remain largely unclear. In the present work, we employed a mechanical stimulus to an individual BV-2 microglia to simulate localized injury. Remarkable ICW propagation was observed no matter whether calcium was in the environment or not. Apyrase (ATP/ADP-hydrolyzing enzyme), suramin (broad-spectrum P2 receptor antagonist), 2-APB (IP(3) receptor blocker) and thapsigargin (endoplasmic reticulum calcium pump inhibitor) potently inhibited these ICWs, respectively, indicating the dependence of nucleotide signals and P2Y receptors. Then, we detected the involvement of five naturally occurring nucleotides (ATP, ADP, UTP, UDP and UDP-glucose) by desensitizing receptors. Results showed that desensitization with ATP and ADP could block ICW propagation in a dose-dependent manner, whereas other nucleotides had little effect. Meanwhile, the expression of P2Y receptors in BV-2 microglia was identified and their contributions were analyzed, from which we suggested P2Y(12/13) receptors activation mostly contributed to ICWs. Besides, we estimated that extracellular ATP and ADP concentration sensed by BV-2 microglia was about 0.3 μM during ICWs by analyzing calcium dynamic characteristics. Taken together, these results demonstrated that the nucleotides ATP and ADP were predominant signal transmitters in mechanical stimulation-induced ICW communication through acting on P2Y(12/13) receptors in BV-2 microglia.